Human resource development in a changing environment - Sharma, Motilal; Mishra, R. K.; Ravishankar, S. (Dhruv & Deep Books, 1988)
Contributed articles.
Includes bibliographies.
Contributed articles.
Keywords: Manpower planning. / http://id.loc.gov/authorities/subjects/sh85080625